Inadvertent Inguinal Sarcoma Excision during Hernia Surgery: Outcomes, Gender Analysis, and Prevention. (7th December 2020) - Lawrenz, Joshua M.; Norris, James P.; Tan, Marcus C.; Shinohara, Eric T.; Block, John J.; Davis, Elizabeth J.; Keedy, Vicki L.; Halpern, Jennifer L.; Holt, Ginger E.; Schwartz, Herbert S.
Abstract : Introduction . Inadvertent excision of a soft tissue sarcoma during hernia surgery is a preventable clinical scenario that leads to unnecessary patient morbidity. Prior series are few, which only include male patients with little focus on prevention. The purpose of this study is to report the presenting features and outcomes of both male and female patients who underwent inadvertent inguinal sarcoma excision during hernia surgery. Methods . A retrospective analysis of a single sarcoma referral center identified 33 patients who were referred for definitive treatment. Patients were divided into three clinically relevant groups based on intraoperative diagnosis, sex, and location of the mass relative to the inguinal ligament. T -tests and Fisher's exact tests were performed to compare continuous and categorical variables, respectively. Kaplan–Meier modeling was performed to assess sarcoma-specific survival. Results . Females were younger (47 years vs. 61 years, p = 0.003 ) and had smaller sarcomas (6.7 cm vs. 11 cm, p = 0.012 ) compared to males. Only two sarcomas (2/33, 6%) were <4 cm in size. The majority of sarcomas in females were above the inguinal ligament (12/14, 86%). Twenty-nine (88%) underwent definitive R0 excision. The mean number of surgeries per patient was three (range 1–13), with nineteen (58%) patients requiring flap reconstruction and six (18%) requiring vascular bypass. Five patients locally recurred (15%) at a mean of 38 months after definitive excision (range 5–128 months). Overall sarcoma-specific disease-free survival was 64%, with no difference between males (80 ± 11%) and females (59 ± 17%) (p = 0.885 ). Mean follow-up was 75 months (range 5–212). Conclusion . This is the second largest study regarding inadvertent inguinal sarcoma excision and the first to include females. When a suspected hernia is >4 cm, irreducible, firm, and is growing, especially in females, consider obtaining preoperative advanced three-dimensional imaging (CT or MRI) that can differentiate a neoplasm from a hernia.